Lupus Nephritis: Glycogen Synthase Kinase 3β Promotion of Renal Damage Through Activation of the NLRP3 Inflammasome in Lupus‐Prone Mice. Issue 4 (April 2015) - Zhao, Jijun; Wang, Hongyue; Huang, Yuefang; Zhang, Hui; Wang, Shuang; Gaskin, Felicia; Yang, Niansheng; Fu, Shu Man
Abstract : Objective: Glycogen synthase kinase 3β (GSK‐3β) has been demonstrated to be involved in immune and inflammatory responses via multiple signaling pathways, leading to the production of proinflammatory cytokines. The purpose of this study was to investigate the role of GSK‐3β in the pathogenesis of lupus nephritis in 2 mouse models. Methods: Thiadiazolidinone 8 (TDZD‐8), a selective inhibitor of GSK‐3β, was administered intraperitoneally to 12‐week‐old MRL/ lpr mice for 8 weeks or to 22‐week‐old (NZB × NZW)F1 mice for 12 weeks. The expression of GSK‐3β and NLRP3 inflammasome components was analyzed. Proteinuria, biochemical parameters, proinflammatory cytokines, anti–double‐stranded DNA (anti‐dsDNA) antibody levels, and renal pathology were examined. In vitro, the effect of GSK‐3β–directed small interfering RNA (siRNA) on NLRP3 inflammasome activation was evaluated in bone marrow–derived macrophages (BMMs) from the mice and in the J774A.1 macrophage cell line. Results: The incidence of severe proteinuria and renal inflammation was significantly attenuated in both models, with a significant reduction in anti‐dsDNA antibody production, immune complex deposition in the kidney, and circulating proinflammatory cytokine levels. TDZD‐8 inhibited the activation of GSK‐3β and caspase 1, with a concomitant decrease in interleukin‐1β (IL‐1β) synthesis. In vitro, GSK‐3β siRNA transfection of mouse BMMs and the J774A.1 cell line with GSK‐3β siRNA inhibited the expression of GSK‐3β, the activation of caspase 1, and the production of IL‐1β. Conclusion: These results show that GSK‐3β promotes lupus nephritis at least partly by activating the NLRP3/IL‐1β pathway. The linking of GSK‐3β to the NLRP3/IL‐1β pathway is a novel observation in our study. Our results suggest that the GSK‐3β/NLRP3/IL‐1β pathway may be a potential therapeutic target for lupus in humans.